Effectiveness Patrol Wheel 2 Unit Same use Reducing the Criminal Act of Theft by Aggregation in Served Law Police Office Gresik - Aqshal, Daffa; Novena Monalisa Sinaga, Theresia; Yusuf Ramadhan, Sardika (Tanggon Kosala, 2025)
Gresik Regency has various crime cases; one of the cases that has increased significantly is aggravated theft. The Objective study is a description of the general implementation of wheel patrol 2 units in reducing criminal acts of aggravated theft in the jurisdiction of the Gresik Police and what the factors that influence the implementation of 2-wheeled patrols in reducing criminal acts of aggravated theft in the jurisdiction of the Gresik Police. The study used draft optimization, Samapta, the Patrol Concept, and the concepts of theft and aggravation. This study used that the management theory and SWOT theory (Strength, Weakness, Opportunities, and Threads). The method of this study was qualitative research with the type of field research. The data sources used are primary data and secondary data. The informants in this study were the KaPolres, Kasat Samapta, KBO Samapta, Kanit Patrol, Sat Samapta Members, and the Community. Data collection techniques in this study are interview and observation and technique analysis data, which used data reduction, data presentation, and conclusion. Implementation of the performance of the Gresik Police Samapta unit in handling the number of theft cases with weighting Not yet effective because of source Power man Still Not yet by list of personnel so that the quality of personnel is not evenly distributed. Another obstacle is the lack of facilities and infrastructure to support such damage. However, the Gresik Police Samapta unit has made several efforts to ensure that performance continues to run, namely by cooperating with the local police in conducting routine patrols and creating reports related to damaged facilities and infrastructure so that they can be reported and repaired.